Research of Spatial Domain Image Digital Watermarking Payload. (14th March 2011) - Jia-Fa, Mao; Ru, Zhang; Xin-Xin, Niu; Yi-Xian, Yang; Lin-Na, Zhou
Abstract : Watermarking payload is a topic in which the watermarking researchers have a great interest at present. Based on the constraint of "perceptual invisibility, " this paper makes a study of the maximum watermarking payload of spatial domain image, which is related to not only embedding intensity, but also to factors such as the size of image, image roughness and visual sensitivity, and so forth. The correlation among the maximum payload and the embedding intensity and size of an image is theoretically deduced through the objective estimation indicator of the peak signal to the noise rate (PSNR) while the relationship model among watermarking payload and image roughness and visual sensitivity is deduced through effective experiments designed on the basis of subjective estimation indicators. Finally, taking all these relationship models into account, this paper proposes a watermarking payload estimation method and verifies its effectiveness through experiments.